A systematic review and meta-analysis comparing surgical and oncological outcomes of upper rectal, rectosigmoid and sigmoid tumours. Issue 9 (September 2021) - Morarasu, Stefan; O'Brien, Luke; Clancy, Cillian; Dietrich, Daniel; Maurer, Christoph A.; Frasson, Matteo; Garcia-Granero, Eduardo; Martin, Sean T.
Abstract: Aim: Management paradigms for tumours from the sigmoid colon to the lower rectum vary significantly. The upper rectum (UR) represents the transition point both anatomically and in treatment protocols. Above the UR is clearly defined and managed as colon cancer and below is managed as rectal cancer. This study compares outcomes between sigmoid, rectosigmoid and UR tumours to establish if differences exist in operative and oncological outcomes. Methods: Electronic databases were searched for published studies with comparative data on peri-operative and oncological outcome for upper rectal and sigmoid/rectosigmoid (SRS) tumours treated without neoadjuvant radiation. The search adhered to PRISMA guidelines (Preferred Reporting Items in Systematic Reviews and Meta-analyses) guidelines. Data was combined using random-effects models. Results: Seven comparative series examined outcomes in 4355 patients. There was no difference in ASA grade (OR, 1.28; 95% CI, 0.99–1.67; P = 0.06), T3/T4 tumours (OR, 1.24; 95% CI, 0.95–1.63; P = 0.12), or lymph node positivity (OR, 0.97; 95% CI, 0.70–1.36; P = 0.87). UR cancers had higher rates of operative morbidity (OR, 0.72; 95% CI, 0.55–0.93; P = 0.01) and anastomotic leak (OR, 0.47; 95% CI, 0.31–0.71; P = 0.0004). There was no difference in local recurrence (OR, 0.63; 95% CI, 0.37–1.08; P = 0.10). SRS tumours had lower rates of distant recurrence (OR, 0.83; 95% CI, 0.68–1.0; P = 0.05). Rectosigmoid operative and cancer outcomes were closer to UR than sigmoid. Conclusions: Based on existing data, UR and rectosigmoid tumours have higher morbidity, leak rates and distant recurrence than more proximal tumours. Highlights: Upper rectal tumours have higher leak rates and morbidity to sigmoid tumours. Upper rectal cancers have higher distant recurrence rates to sigmoid tumours. Rectosigmoid tumours assessed alone appear to share similar outcomes to upper rectal cancers.